Low frequency of enterohemorrhagic, enteroinvasive and diffusely adherent Escherichia coli in children under 5 years in rural Mozambique - Garrine, Marcelino (2020)
Funding information: The GEMS was funded by the Bill & Melinda Gates Foundation and coordinated by the Center for Vaccine Development, University of Maryland School of Medicine under the grant (OPP1033572). CISM receives core funding from Spanish Agency for International Cooperation and Development (AECID - Agencia Espanola de Cooperacion Internacional para el Desarollo) and the Government of Mozambique. Marcelino Garrine has a scholarship from Calouste Gulbenkian Foundation "Fundacao Calouste Gulbenkian" (grant number: 145278). The funders had no role in the study design, collection, analysis and interpretation of data, and manuscript writing.